Cutaneous emperipolesis: Rosai-Dorfman disease - An uncommon entity - M B Shashi Kumar; Savitha A Somaiah; Murali Mohan; Rakshith Vittal (Wolters Kluwer Medknow Publications, 2023)
Rosai-Dorfman disease (RDD) is a rare, benign idiopathic, non-Langerhans cell histiocytosis. The most common presentation is massive bilateral painless lymphadenopathy with fever and weight loss. Approximately 40% of patients with RDD have extranodal involvement. The cutaneous involvement is the most common extranodal manifestation comprising 11% of RDD, but only 3% presents as pure cutaneous disease (CRDD). A 55-year-old male presented with a painless swelling over the neck in the midline of 2 months duration. On examination, a firm nodular lesion measuring 1 cm × 1 cm was located on the midline of the neck. Excision biopsy was done with a differential diagnosis of calcified cyst. Histopathological examination showed emperipolesis, and immunohistochemistry was positive for S 100 and cluster of differentiation (CD) 68 and negative for CD1a confirming a diagnosis of RDD. All systemic, biochemical, and radiological examinations were unremarkable. There was no further local recurrence after 1 year of follow-up.